The perception of EFL student teachers on the teaching and use of critical thinking - Mohammad Hasbullah Isnaini; Esti Junining; Widya Caterine Perdhani (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2021)
Critical thinking (CT) is crucial for the aspect in English language education, yet little attention has been given to language teacher’s perception an experience regarding CT during the pre-service of their teaching career. The data of the present study were gained from the focus group discussion and interview which covered the participants’ understanding of CT and its use in the teaching and learning process. The study indicates that the participants had limited understanding of CT, they need more support to be able to apply CT properly in their teaching process, and they also faced contextual challenges when integrating CT into their teaching. The study suggests that critical mindset should be cultivated among the student-teachers, so that they can develop proper CT-oriented pedagogies.